CURRENT UNDERSTANDING OF THE TREATMENT OF PATIENTS WITH INJURIES OF THE INTERTROCHANTERIC SYNDESMOSIS (LITERATURE REVIEW) - Gafurov Farrukh Abualievich; Iskandar Yunusovich Khojanov; Sherzod Nuralievich Eranov; Ergash Rakhmatullaevich Mukhammadiev (Scholar Express Journals, 2022)
Treatment of patients with ankle fractures with rupture of the intertibial syndesmosis is an unsolved problem of modern traumatology. The classification and history of the development of conservative and surgical treatment of ankle joint injuries with a detailed analysis of the designs, types, and complications of their use are presented
Keywords: Ankle Joint; Intertibial Syndesmosis; Submerged Osteosynthesis; External Fixation Device